Taxonomic Synopsis of the genus Chamaecrista (Leguminosae, Caesalpinioideae) in the Chapada dos Veadeiros region, Goiás, Brazil - Souza, Alessandro Oliveira De; Lewis, Gwilym Peter; Silva, Marcos José Da (Phytotaxa, 2019)
Chamaecrista is one of the largest genera of Leguminosae subfamily Caesalpinioideae and comprises 330 species, of these, 222 species are present in the Phytogeographic Cerrado Domain in Brazil. The taxonomy of the genus in Brazil continues to need study. Here we present a taxonomic synopsis of Chamaecrista for the Chapada dos Veadeiros (CV) region, which is located in the northern portion of the state of Goiás, Brazil. Fieldwork was carried out in the area between 2010 and 2018; we also reviewed the literature and about 1500 herbarium collections to build the synopsis of species presented here. We record 65 species (71 taxa) of Chamaecrista occurring in the CV, corresponding to 60% of the species registered for the state of Goiás; 49 species at Chapada dos Veadeiros National Park (CVNP), 27 and 19 are endemic to the state of Goiás and the studied area respectively. An identification key and distribution maps, as well as comments on morphology and conservation status are presented, together with photograhs of the species in the field.